Aspirin eugenol ester ameliorates LPS-induced inflammatory responses in RAW264.7 cells and mice - Liu, Xu; Tao, Qi; Shen, Youming; Liu, Xiwang; Yang, Yajun; Ma, Ning; Li, Jianyong (Frontiers in Pharmacology, 2023)
Introduction: Inflammation is a defensive response of the body and the pathological basis of many diseases. However, excessive inflammation and chronic inflammation impair the homeostasis of the organism. Arachidonic acid (AA) has a close relationship with inflammation and is the main mediator of the pro-inflammatory response. Based on the prodrug principle, the new pharmaceutical compound aspirin eugenol ester (AEE) was designed and synthesized. However, the effects of AEE on key enzymes, metabolites and inflammatory signaling pathways in the AA metabolic network have not been reported. Methods: In this study, the anti-inflammation effects of AEE were first investigated in mice and RAW264.7 cells in LPS induced inflammation model. Then, the changes of the key enzymes and AA metabolites were explored by RT-PCR and targeted metabolomics. Moreover, the regulatory effects on NF–kB and MAPKS signaling pathways were explored by Western Blotting. Results: Results indicated that AEE significantly reduced the number of leukocyte and increased the lymphocyte percentage. AEE decreased the expression levels of IL-1β, IL-6, IL-8 and TNF-α both in vivo and in vitro. In the liver of mice, AEE downregulated the levels of AA, prostaglandin D2 (PGD2) and upregulated 12- hydroxyeicosatetraenoic acid (12-HETE). However, the changes of PGE2, PGF2α, 6-keto-prostaglandin F1α (6-KETO-PGF1α), 9-hydroxy-octadecenoic acid (9- HODE), 13-HODE, 15-HETE, docosahexaenoic acid (DHA) and thromboxane B2 (TXB2) were not significant. Additionally, it was found that AEE decreased the relative mRNA expression levels of p65 and p38 and the ratio of p-p65/p65. Discussion: It was concluded that AEE might inhibit the LPS-induced inflammatory response through the regulation of AA metabolism. This study provides the theoretical foundation for the development of AEE as a medicinal anti-inflammatory drug.